Adjunctive mesenchymal stem/stromal cells augment microvascular function in poststenotic kidneys treated with low‐energy shockwave therapy. Issue 12 (19th May 2020) - Chen, Xiao‐Jun; Zhang, Xin; Jiang, Kai; Krier, James D.; Zhu, Xiangyang; Conley, Sabena; Lerman, Amir; Lerman, Lilach O.
Abstract: Effective therapeutic strategies are needed to preserve renal function in patients with atherosclerotic renal artery stenosis (ARAS). Low‐energy shockwave therapy (SW) and adipose tissue‐derived mesenchymal stem/stromal cells (MSCs) both stimulate angiogenesis repair of stenotic kidney injury. This study tested the hypothesis that intrarenal delivery of adipose tissue‐derived MSCs would enhance the capability of SW to preserve stenotic kidney function and structure. Twenty‐two pigs were studied after 16 weeks of ARAS, ARAS treated with a SW regimen (bi‐weekly for 3 weeks) with or without subsequent intrarenal delivery of adipose tissue‐derived MSCs and controls. Four weeks after treatment, single‐kidney renal blood flow (RBF) before and after infusion of acetylcholine, glomerular filtration rate (GFR), and oxygenation were assessed in vivo and the renal microcirculation, fibrosis, and oxidative stress ex vivo. Mean arterial pressure remained higher in ARAS, ARAS + SW, and ARAS + SW + MSC compared with normal. Both SW and SW + MSC similarly elevated the decreased stenotic kidney GFR and RBF observed in ARAS to normal levels. Yet, SW + MSC significantly improved RBF response to acetylcholine in ARAS, and attenuated capillary loss and oxidative stress more than SW alone. Density of larger microvessels was similarly increased by both interventions. Therefore, although significant changes in functional outcomes were not observed in a short period of time, adjunct MSCs enhanced pro‐angiogenic effect of SW to improve renal microvascular outcomes, suggesting this as an effective stratege for long‐term management of renovascular disease. Abstract : Effective therapeutic strategies are needed to preserve renal function in patients with atherosclerotic renal artery stenosis (ARAS). The current study shows that addition of MSCs improves density of capillaries and microvascular endothelial function in vivo in SW‐treated stenotic kidneys, possibly by increasing nitric oxide bioavailability, decreasing renal oxidative stress, and upregulating anti‐inflammatory mediators.